Muitas águas: Despertar feminino e imaginário poético – figurações de Anima em Magma e em “A estória de Lélio e Lina” - Rocha, Hélen Cristina Pereira Rocha (2023)
This thesis analyses João Guimarães Rosa’s poetic work, Magma (1997), with the intention of tracing the feminine aspect of his poems, seeking to prove its fecund feature in the prose of the mineiro writer. Rosa’s poetic process is composed of an aesthetic that benefits from a mythical-symbolic language that brings out an archetypal figuration expressed through elements such as water, earth, night, and moon. Thus, an analysis of Magma's poems is proposed, aiming to define how Guimarães Rosa forges, in these poems, in an even more subtle way than in prose, a way of approaching the feminine as an unconscious creator, as an essential core from which emanates life. Therefore, it starts from the hypothesis that, in his poems, Rosa seems to evidence the manifestation of “female power” from images that refer to the creative, unconscious, and fecund power of women. So that, it will seek to demonstrate how Magma's poems introduce a theme that will be bluntly developed by Rosa in his narratives, and in this thesis, it will specifically refer to one of his novels that belongs to the book No Urubuquaquá, no Pinhém, “A história de Lélio e Lina” (2001). It will take as a theoretical contribution, to support this work, both the symbolic imaginary element, as well as the collective unconscious aspects that permeate the poetic of Guimarães Rosa, the studies by Carl Gustav Jung, Gaston Bachelard, Gilbert Durand and Mircea Eliade. At the end of the discussions, it will demonstrate, in the Guimarães Rosa’s poetic, a lyricism marked by the presence of a phenomenological symbology that points to the existence of female archetypes that rise in the face of the telluric theme developed in the poems.